The Effect of Deep Breathing Techniques on Reducing Menstrual Related Stress Among Students of SMPN 2 Rambutan, Banyuasin Regency - Tri Sartika; Ayu Devita Citra Dewi (Jurnal Ventilator, 2025)
Stress among early adolescent girls in junior high school is an increasing health concern due to academic demands, social pressure, digital exposure, and menstrual related discomforts. Complementary interventions such as deep-breathing techniques offer a simple method that can be implemented in school settings to rapidly reduce stress. This study aimed to examine the effect of deep-breathing techniques on menstrual related stress among ninth-grade female students at SMPN 2 Rambutan, Banyuasin Regency.  A pre-experimental one-group pretest–posttest design was used. The sample consisted of 60 students selected from the ninth-grade population. Stress levels were measured using the Perceived Stress Scale (PSS-10) focusing on stress during menstruation before and after a single deep-breathing session. Data were analyzed using the Wilcoxon test. The results showed a significant reduction in stress scores after the intervention (p < 0.001). The proportion of students in the high-stress category decreased from 20% to 6.7%, while those in the low-stress category increased from 10% to 30%. The mean stress score decreased from 21.35 ± 4.82 to 15.42 ± 4.11. This study concludes that deep-breathing techniques are effective in reducing menstrual-related stress in female students within a single session and can be recommended as a complementary strategy that is easy to implement in schools for adolescent menstrual stress management.